Effect of Nitrogen Fertilization on the Quality of Swiss Chard at Harvest and during Storage as Minimally Processed Produce. Issue 2 (27th February 2014) - Miceli, Alessandro; Miceli, Claudia
Abstract The effects of different levels of nitrogen fertilization (0–50–100–150–200 kg/ha), minimal processing and cold storage (14 days at 4C) on yield and quality of fresh‐cut Swiss chard (Beta vulgaris L. var. cicla L.) were evaluated. Increasing the level of nitrogen fertilization over 100 kg N/ha, plants had a higher fresh weight, reduced their dry matter content and resulted taller and leafier. Total and marketable yield increased linearly with increasing nitrogen level. Both nitrate and ascorbic acid content at harvest increased with increasing nitrogen supply. Nitrogen fertilization negatively affected the yield of minimal processing. No effect on appearance and quality loss during cold storage was detected. Reducing nitrogen fertilization could lead to a more environmentally friendly product with no significant loss in yield and quality both for raw plant and fresh‐cut Swiss chard. Minimal processing can improve nutritional quality lowering nitrates and increasing ascorbic acid content in fresh‐cut produce. Practical Applications Minimally processed vegetables have gained a lot of interest among consumers as they are easy to use and ready to eat. Leafy vegetables are the most widespread among fresh‐cut produce. In order to increase the yield and the quality of leafy crops, farmers often supply great amounts of nitrogen fertilizers. Overdoses of nitrogen may negatively affect environment and nutritional quality of raw and minimally processed vegetables. This study focused on the assessment of the dose of nitrogen that can be more environmentally friendly and can assure to the industry of minimal processing, the best quality of raw Swiss chard and the retaining of good quality during storage. The reduction of nitrogen fertilization may lead to a reduction in nitrate content of the plants and, if associated to minimal processing, determines an improvement of the nutritional quality of fresh‐cut Swiss chard.